Exploring Azadirachta indica’s Potential to Combat Visceral Leishmaniasis Through GP63 Inhibition - Mohammed Abrar (International Journal of Genetic Modifications and Recombinations, 2024)
Objectives: Millions of people worldwide suffer from the parasite disease visceral leishmaniasis. Determine the naturally occurring active ingredients in Azadirachta indica, which are employed as a disease-prevention agent and have several uses in medicine. To choose the best ligand to use as a medication, absorption, distribution, metabolism, and excretion (ADME) studies and molecular docking are employed. Methods: To obtain the GP63 protein, the Protein Data Bank (PDB) database was accessed. The IMPPAT database was utilised to obtain phytocompounds. The pharmacokinetic characteristics of these drugs were evaluated using in silico ADME analysis. PyRx is used for molecular docking. Results: Molecular docking analysis revealed promising interactions between the selected Azadirachta indica phytocompound and the GP63 protein, indicating its potential as inhibitor of Leishmania parasite virulence. 6-Deacetylnimbin demonstrated significant binding affinity with GP63, warranting further investigation. Furthermore, the phytocompound exhibited favourable pharmacokinetic properties, suggesting their suitability for drug development. Conclusion: The phytocompound 6-Deacetylnimbin exhibits a promising binding affinity with the GP63 protein, making it a potential therapeutic candidate for the treatment of visceral leishmaniasis.
Keywords: ADMET analysis; Azadirachta indica; GP63; Phytocompound; molecular docking; visceral leishmaniasis